BASIC: a new Biopart Assembly Standard for Idempotent Cloning provides accurate, single-tier DNA assembly for synthetic biology - Storch,M; Casini,A; Mackrow,B; Fleming,T; Trewhitt,H; Ellis,T; Baldwin,GS (ACS Synthetic Biology, 2015)
The ability to quickly and reliably assemble DNA constructs is one of the key enabling technologies for synthetic biology. Here we define a new Biopart Assembly Standard for Idempotent Cloning (BASIC), which exploits the principle of orthogonal linker based DNA assembly to define a new physical standard for DNA parts. Further, we demonstrate a new robust method for assembly, based on type IIs restriction cleavage and ligation of oligonucleotides with single stranded overhangs that determine the assembly order. It allows for efficient, parallel assembly with great accuracy: 4 part assemblies achieved 93% accuracy with single antibiotic selection and 99.7% accuracy with double antibiotic selection, while 7 part assemblies achieved 90% accuracy with double antibiotic selection. The linkers themselves may also be used as composable parts for RBS tuning or the creation of fusion proteins. The standard has one forbidden restriction site and provides for an idempotent, single tier organisation, allowing all parts and composite constructs to be maintained in the same format. This makes the BASIC standard conceptually simple at both the design and experimental levels.